Analisis Media Pembelajaran Anak Usia Dini Berbasis Teknologi Masa Pandemi Covid-19 - Pujiati, Desti; Yulianto, Dema (Universitas Nusantara PGRI Kediri, 2021)
IT (Information Technology) in education sector during the Covid-19 pandemic becomes great challenges. Information technology among education, educators and school programs are still interesting subjects to discuss. The internet quota from the Ministry of Education and Culture is an effort to help the students in learning process starts from Kindergarten up to Higher level. Combined research method and purposive sampling technique are used in this study. Distributing questionnaires and conducting interviews are implemented to collect the data. In learning process during the Covid-19 pandemic, the teachers or educators in Banyumas Regency began to develop and deepen their much needed capabilities of Information Technology. The results showed that the utilization of IT in Banyumas Regency has already been well provided, had a good internet connection, and gainned quota from the Ministry of Education and Culture. Media can be used are cell phones, laptop, social media such as Facebook, Instagram, whatsapp group, email, zoom, and google meet. Every effort was done to make the education success in every sub-district at Banyumas Regency. From the data obtained, almost 65% used Whatsapp Group effectively through video from cell phone, 20% through Instagram, 5% through YouTube, 5% through zoom, and 5% through google meet. In line with 21st century of education expert has four skills in active communication, collaborative, higher order thinking and problem solving related to education. There are also some other efforts can be done such as increasing learning and developing educational creativity. The success of learning in each component is able to influence each other.